Analisis Pengaruh Opini Audit, Ukuran KAP, Ukuran Perusahaan, Dan Pergantian Manajemen Perusahaan Terhadap Pergantian KAP (Studi Empiris Perusahaan Mining Dan Mining Services Yang Terdaftar Di BEI Tahun 2010 - 2014) - Adiguna, Sofiyan (2016)
This study aims to determine the factors that influence the factors that influence the turn of KAP. Variables used in this research is the audit opinion, firm size, firm size, and management changes. This study uses data from the financial statements of companies mining and mining services listed in Indonesia Stock Exchange 2010-2014. By using purposive sampling method the number of samples obtained, totaling 26 companies. The analytical tool used in this research is logistic regression. Based on analysis of data obtained, it can be concluded that the size of the variable effect on turnover KAP KAP. This is evidenced by the p-value 0.013 sebsesar so that H2 is accepted with a significance level (P = 0.05). Furthermore, other variables in this study as the audit opinion, the size of the company, and management changes did not affect the change of KAP. Keywords: Substitution KAP, audit opinion, firm size, firm size, and management changes